1984
DOI: 10.1007/bf00120534
|View full text |Cite
|
Sign up to set email alerts
|

Transport of gases and particles to surfaces with widely spaced roughness elements

Abstract: Radioactive gases and labelled particles have been used in wind tunnels to measure the effects of Reynolds and Schmidt numbers on transport to surfaces with widely spaced roughness elements. Good correlations are obtained for gases and for sub-micrometric sized particles, and the results can probably be extended to conditions in the open air. Deposition oflarger particles is dominated by the effects of bounce off, which depends on surface conditions. This is also reflected in the pattern of deposition between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

1986
1986
2007
2007

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 12 publications
(13 reference statements)
0
20
0
Order By: Relevance
“…When particle deposition is the concern, quantification of surface roughness is needed rather than simple classification of the surface as hydraulically smooth. Macroscale roughness, in the form of fibers or grasses (Chamberlain, 1967;Wells & Chamberlain, 1967;Sehmel, 1970a), repeated ribs (Chamberlain et al, 1984;Hahn et al, 1985;Lai, 1997) and uniform three-dimensional elements (Lai, 1997), has been more frequently characterized and its influence on deposition more systematically investigated. Roughnesses reported in Tables 2.2-2.5 include both microscale and macroscale conditions.…”
Section: Details About Experiments In Straight Tubes and Ductsmentioning
confidence: 99%
See 2 more Smart Citations
“…When particle deposition is the concern, quantification of surface roughness is needed rather than simple classification of the surface as hydraulically smooth. Macroscale roughness, in the form of fibers or grasses (Chamberlain, 1967;Wells & Chamberlain, 1967;Sehmel, 1970a), repeated ribs (Chamberlain et al, 1984;Hahn et al, 1985;Lai, 1997) and uniform three-dimensional elements (Lai, 1997), has been more frequently characterized and its influence on deposition more systematically investigated. Roughnesses reported in Tables 2.2-2.5 include both microscale and macroscale conditions.…”
Section: Details About Experiments In Straight Tubes and Ductsmentioning
confidence: 99%
“…Their data confirmed the expected decrease in deposition with increases in particle size within the diffusion regime until Brownian diffusion becomes negligible. Chamberlain et al (1984) made a single observation of deposition in the diffusion regime. Shimada et al (1993) provided a larger data set of reasonable quality for deposition in the diffusion regime, showing increasing deposition for decreasing particle size.…”
Section: 33a Particle Size and Air Velocitymentioning
confidence: 99%
See 1 more Smart Citation
“…Chamberlain, Garland, and Wells (1984) found that transfer correlated well with: This relationship is based on lead-121 and iodine-131 data.…”
Section: 34mentioning
confidence: 90%
“…Several empirical formulae have been proposed for excess resistance (and, therefore, implicitly z p ) under different conditions (e.g. Thom 1972;Stewart and Thom, 1973;Brutsaert, 1982;Chamberlain, 1984) Fortunately, investigation of the effective value of z p (e.g. Garratt and Francey, 1978) for a range of surfaces covered in permeable (fibrous) vegetation has suggested that ln(z 0 /z p ) ~ 2 (Fig.…”
Section: Fig 4 Conceptual Framework Of the Rutter Model (Rutter Et mentioning
confidence: 99%